Modelling Based Business Process Improvement - Seidov, Murat; Řepa, Václav, 1958-; Svatoš, Oleg; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The objective of this thesis is to review the Methodology for Modeling and Analysis of Business Process (MMAPB) and apply MMAPB knowledge to solve real-world organization case. Firstly, the author will define business processes and way to describe real world into business processes, provide information about the Methodology for Modeling and Analysis of Business Process to provide enough context for application in the real-world use case. Secondly, for selected organization the author will review the existing business process and attempt to improve them with MMAPB best practices. The application process will consist of the analysis, implementation and session with the organization management to provide feedback and review of the applied changes.
Vedoucí práce: Václav Řepa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses